Developmental Coordination Disorder in a Patient with Mental Disability and a Mild Phenotype Carrying Terminal 6q26-qter Deletion - De Cinque, Marianna; Palumbo, Orazio; Mazzucco, Ermelinda; Simone, Antonella; Palumbo, Pietro; Ciavatta, Renata; Maria, Giuliana; Ferese, Rosangela; Gambardella, Stefano; Angiolillo, Antonella; Carella, Massimo; Garofalo, Silvio (Frontiers in Genetics, 2017)
Terminal deletion of chromosome 6q is a rare chromosomal abnormality associated with variable phenotype spectrum. Although intellectual disability, facial dysmorphism, seizures and brain abnormalities are typical features of this syndrome, genotype-phenotype correlation needs to be better understood. We report the case of a 6-year-old Caucasian boy with a clinical diagnosis of intellectual disability, delayed language development and dyspraxia who carries an approximately 8 Mb de novo heterozygous microdeletion in the 6q26-q27 locus identified by karyotype and defined by high-resolution SNP-array analysis. This patient has no significant structural brain or other organ malformation, and he shows a very mild phenotype compared to similar 6q26-qter deletion. The patient phenotype also suggests that a dyspraxia susceptibility gene is located among the deleted genes.